Physical, psychological and economic burden of two-wheel users after a road traffic injury: Evidence from intensive care units of three EU countries. (December 2018) - Papadakaki, Maria; Tsalkanis, Angelos; Sarris, Markos; Pierrakos, George; Eleonora Ferraro, Ottavia; Stamouli, Maria-Angeliki; Orsi, Chiara; Otte, Dietmar; Tzamalouka, Georgia; Lajunen, Timo; Özkan, Türker; Morandi, Anna; et al.
Abstract: Introduction : This study aimed to assess the physical, psychological, and economic burden shouldered by severely injured two-wheel users in three European countries as well as the cost resulting from their hospitalization. Methods : A total of seven public hospitals were involved in three countries: Greece, Italy, and Germany. Participants enrolled during a 12-month period starting in April 2013. Eligibility criteria included an injury sustained at Road Traffic Crashes (RTC) irrespective of the type of vehicle, hospitalization 1 day in the Intensive Care Unit (ICU) or sub-ICU, and age 18 years or over. Patients were interviewed at 1, 6, and 12 months upon admission. The study used widely recommended classifications for injury severity (Abbreviated Injury Severity [AIS]; Maximum Abbreviated Injury Severity [MAIS]) and standardized measures such as the Disability Assessment Schedule II (WHODAS 2.0), "Impact of Event Scale" (IES-R), Center for Epidemiological Studies Depression Scale (CES-D Scale). Health Care Expenditure was assessed through the Monash University Accident Research Centre (MUARC's) framework, which included measures of 'Direct' and 'Indirect' costs. Diagnosis-related groups (DRGs) were used to estimate hospitalization costs. Results : A total of 54 two-wheel users enrolled in the study in all the countries and 32 completed all follow-up questionnaires. Physical disability increased over 12 months following the injury. Post Traumatic Stress Disorder (PTSD) symptoms of avoidance remained at high levels over the study period. PTSD symptoms of intrusion improved significantly during the second half of the year under investigation. The total annual cost of injury for the two-wheel users who were hospitalized in the selected ICU of all the partner countries for severe injury in 2013/2014, was estimated at €714, 491 made up of €123, 457 direct and €591, 034 indirect costs. Men, aged 50–64 years and those who sustained slight injuries primarily at the lower extremities presented higher indirect costs per person. A total of €1032.092 was spent on hospitalization payments. Women, aged 65 + and those who sustained severe injuries at the central body region presented higher direct costs per person. Women, aged 50–64 years, those with severe injuries and a major injury at the central body and the upper body region presented the highest hospitalization costs per person. Conclusions : There is a need for effective strategies to early detect and treat groups at risk of being confronted with prolonged psychosocial and economic consequences. Practical implications : A holistic understanding of the impact of injury on individuals is important in order to achieve effective treatment of psychological co-morbidities in a timely manner. Highlights: Injury in two-wheel users is responsible for an enormous burden to governments and individuals across the three countries. Personal characteristics of the most vulnerable two-wheel users have been identified. Indirect costs have far outweighed the direct costs of injury among injured two-wheel users. Longitudinal studies are needed to explore the post-injury effect on two-wheel users through longer periods of time.